Mucosal Mast Cell Count Is Associated With Intestinal Permeability in Patients With Diarrhea Predominant Irritable Bowel Syndrome - Lee, Hyuk; Park, Jung Ho; Park, Dong Il; Kim, Hong Joo; Cho, Yong Kyun; Sohn, Chong Il; Jeon, Woo Kyu; Kim, Byung Ik; Chae, Seoung Wan (Journal of neurogastroenterology and motility, 2013)
Although mucosal mast cell tryptase is known to significantly increase intestinal permeability, the relationship between mucosal mast cells and intestinal permeability remains unclear. The objective of this study was to evaluate the correlation among intestinal permeability, tryptase activity and mucosal mast cell count. Rectal biopsies from 16 patients with diarrhea-predominant irritable bowel syndrome (IBS-D) and 7 normal subjects were assessed for tryptase activity and macromolecular permeability using horseradish peroxidase in Ussing chambers. In addition, mucosal mast cell levels were immunohistochemically quantified via image analysis. Rectal biopsy of tissues from IBS-D patients showed significantly increased permeability compared with those from normal controls (0.644 ± 0.08 and 0.06 ± 0.00 ng/2 hr/mm(2), P < 0.01). Tryptase activity was also substantially higher in rectal biopsy samples from IBS-D patients than those from normal controls (0.86 ± 0.18 and 0.28 ± 0.04 mU/mg protein, P < 0.05). Mucosal mast cell counts were not significantly different between the 2 groups (P > 0.05). However, correlation analysis revealed that only mucosal mast cell count was significantly correlated with intestinal permeability in IBS-D patients (r = 0.558, P < 0.05). This study demonstrated a positive correlation between the number of mucosal mast cells and intestinal permeability, suggesting that mucosal mast cells play an important role for increased intestinal permeability in patients with IBS-D.